Rapid progression to AML in a patient with germline GATA2 mutation and acquired NRAS Q61K mutation. (2019) - McReynolds, Lisa J.; Zhang, Yubo; Yang, Yanqin; Tang, Jingrong; Mulé, Matthew; Hsu, Amy P.; Townsley, Danielle M.; West, Robert R.; Zhu, Jun; Hickstein, Dennis D.; Holland, Steven M.; Calvo, Katherine R.; et al.
Abstract: GATA2 deficiency syndrome is caused by autosomal dominant, heterozygous germline mutations with widespread effects on immune, pulmonary and vascular systems. Patients commonly develop hematological abnormalities including bone marrow failure, myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). We present a patient with GATA2 mutation and MDS who progressed to AML over four months. Whole exome and targeted deep sequencing identified a new p.Q61K NRAS mutation in the bone marrow at the time of AML development. Rapid development of AML is possible in the setting of germline GATA2 mutation despite stable MDS, supporting close monitoring and consideration of early allogeneic transplantation.